Differential Biochemical Responses of Resistant and Susceptible Genotypes of Chili to Pepper Yellow Leaf Curl Thailand Virus - Manthana Mueangkhong; Patcharaporn Suwor; Suchila Techawongstien; Montinee Teerarak; W. S. Tsai; Tanyarat Tarinta; Sanjeet Kumar; Nakarin Jeeatid; Orawan Chatchawankanphanich; Somsak Kramchote (Horticulturae, 2025)
Chili (Capsicum annuum L.) production is threatened by the pepper yellow leaf curl virus (PepLCV), transmitted by whiteflies, leading to reduced yields. This study investigated the biochemical changes in two chili genotypes, PEP6 (tolerant to PepLCV) and Homsuphan (susceptible to PepLCV), following inoculation with the Thailand strain of PepLCV (known as Pepper Yellow Leaf Curl Thailand Virus, PepYLCTHV). Inoculation was performed using whitefly transmission (WF) and graft transmission (GT) methods, and disease severity was evaluated using a standardized index. The level of total phenolic compounds and the activities of peroxidase (POD) and polyphenol oxidase (PPO) enzymes were analyzed in virus-infected plants and compared with those in uninoculated controls. Both chili genotypes exhibited a more rapid increase in disease severity when inoculated with WF than with GT. In PEP6, disease severity was lower than Homsuphan in both WF and GT inoculations. Disease severity in WT-inoculated PEP6 plants increased gradually, reaching 100% by day 36, whereas Homsuphan plants had a more rapid progression, attaining 100% by day 21. The GT method led to slower disease severity progression in both genotypes, reaching 80–85% by day 36. In PEP6 plants, total phenolic compound content increased significantly following WF, indicating an active defense response, whereas levels remained stable in GT plants. Phenolic content in the tolerant genotype Homsuphan remained stable across all conditions. Notably, peroxidase (POD) activity was elevated in GT plants of both genotypes, which correlated with reduced disease severity. Polyphenol oxidase (PPO) activity was lowest in control plants, but WT and GT increased the PPO level. Among the treatments, GT induced the highest PPO activity, which was associated with the lowest disease severity. These findings suggest that GT may enhance disease resistance by modulating phenolic compound accumulation and increasing POD and PPO activity.
Keywords: Plant Virus Research Studies; Plant Disease Management Techniques; Plant-Microbe Interactions and Immunity